KẾT QUẢ NGHIÊN CỨU THÀNH PHẦN LOÀI CHIM TẠI KHU BẢO TỒN THIÊN NHIÊN PÙ HOẠT, TỈNH NGHỆ AN NĂM 2018 - Nguyễn, Hồng Phương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESULTS OF THE RAPID AVIFAUNA SURVEYS IN PU HOAT NATURAL RESERVE, NGHE AN PROVINCEA total of 125 bird species belonging to 39 families and 10 orders have been recorded, of which Passeriformes was the most abundant with 88 species accounting for 70.4%, Piciformes 11 species - 8.8%, Columbiformes 6 species - 4.8%, Accipitriformes and Cuculiformes 5 species - 4%, others order 1 to 3 species, accounting for 11.8%. We confirmed the first record of Collared Treepie for the North Central of Vietnam and adding one more species for the birdlist of Pu Hoat Nature Reserve (Rufous-cheeked Laughingthrush).